Response transmissibility versus power spectrum density transmissibility: Dynamic property analysis and comparison. (18th August 2019) - Li, X.Z.; Yue, X.B.; Dong, X.J.; Peng, Z.K.
Abstract: The concept of transmissibility has been developed rapidly for operational modal analysis (OMA) in recent years. In general, there are two kinds of transmissibility: response transmissibility (RT) and power spectrum density transmissibility (PSDT). Based on these concepts, several approaches have been proposed to identify the modal parameters under operational conditions. However, since no systematic research has been made about the dynamic properties of these concepts, how to select the right transmissibility suited for the current operating condition is difficult. PSDT based OMA methods reduce the number of input conditions in RT based methods to single one. But, it is still confused that whether the PSDT based OMA methods are input spectrum independent under all kinds of input conditions. Therefore, dynamic properties of transmissibility are analyzed systematically in this paper. The inputs are classified into discrete input and distributed inputs according to the number of input sources and spatial correlation. Input spectrum independence and convergence value invariance of transmissibility are studied for different input conditions using analytic derivation. Dynamic properties of different kinds of transmissibility are compared, and the relationship between single-reference transmissibility and basic PSDT is discussed. The above conclusions are then validated by numerical simulation and experimental tests. The results show the properties of transmissibility and provide guidance for transmissibility selection in field test. Highlights: Dynamic properties of transmissibility are analyzed systematically. In theory, single-reference transmissibility and basic PSDT are consistent. They have the convergence value invariance for all the input conditions. They have the input spectrum independence under correlation inputs. The PSDT methods are non-deterministic, and are not suit for non-white noise input.